Indonesian Community Active Lifestyle: Between Expectations and Reality - Taupik Rochman; Adang Suherman; Amung Ma’mun; Bambang Abduljabar (Jurnal Maenpo : Jurnal Pendidikan Jasmani Kesehatan dan Rekreasi, 2021)
The active lifestyle of the community becomes a healthy picture of the nation's life because it is one of the keys to maintaining and improving public health. An active lifestyle is defined as a physical activity that is integrated into everyday life, which can be compiled by oneself and the social environment. Indonesia has a society with a physical activity level of 66.5% in the moderate category and a low position. Such conditions occur all over the world so that intervention to improve people's lifestyles has become one of the focuses of world attention in the 2013-2020 action plan called the World Health Organization's best buys. This article aims to describe the efforts made in Indonesia in improving people's lifestyles. The method used is a literature review. However, even though the lifestyle of the Indonesian people is still categorized, the efforts made are by recommendations from the World Health Organization. So that the active lifestyle of the Indonesian people is not only hoping or just a desire to care but is a real thing, really exists and is proven. However, with a high population and a very large area, such a strategy is needed to be well integrated between all levels of society and the government so that it can make an active lifestyle as the strength of the nation in maintaining and improving the quality of life.Keywords: Physical activity, active style, life